Virtual Learning Environment (VLE) in Teaching Writing Skill in Indonesian Higher Education - Nur Insyirah; Muhammad Tahir; Muhammad Basri (International Journal of Language, Education, and Literature, 2025)
This research aims to investigate (1) lecturer’s perception of Virtual Learning Environment (VLE) in teaching writing skill and (2) lecturer’s implementation of Virtual Learning Environment (VLE) in teaching writing skill. The researcher employed a qualitative method with a case study approach. The subjects of the study a lecturer, selected using a purposive sampling technique. The lecturer was selected based on their experience teaching a writing class within a Virtual Learning Environment using both synchronous and asynchronous instructional methods. The data were collected through observations, interviews, and document analysis, and were analyzed using a thematic analysis technique. The data analysis revealed that (1) the lecturer viewed VLE as something positive by its usefulness, ease of use, and flexibility, however also reported some challenges such as poor internet connection, lack of social interaction, and variety of students engagements. (2) The lecturer implemented VLE thoroughly in planning (integrating multimedia resource and having weekly essay assignments), teaching and learning process (keep track on students’ improvements and engagement), and evaluations (flexible media submissions and using writing rubrics score). Moreover, future research involving larger-scale studies is recommended to further explore deeper insights into optimizing virtual teaching methods.